Gene therapy for inherited immunodeficiency. (June 2014) - Touzot, Fabien; Hacein-Bey-Abina, Salima; Fischer, Alain; Cavazzana, Marina
<x xml:space="preserve">Abstract</x> Introduction: During the last decade, gene therapy has emerged as a convincing therapy for primary immunodeficiencies (PIDs). Ex vivo gene transfer into autologous hematopoietic stem cells (HSCs) via viral vectors permits sustained correction of T cell immunodeficiency in two forms of severe combined immunodeficiency: X–linked SCID (SCID-X1) (γ chain [γc] deficiency) and adenosine deaminase deficiency. However, this success has been balanced by the occurrence of genotoxicity generated by the integration of first-generation retroviral vectors. Recently, the development of safer self-inactivating vectors has led to the initiation of new studies with the hope of equivalent efficacy and a better safety profile. Areas covered: This review article focuses on the updated results of gene therapy trials for PIDs – from early studies to ongoing clinical trials. We detail the major advances made in gene transfer and repair technologies, and discuss the many ways to extend our present experience. Expert opinion: With optimization in terms of safety and efficacy, gene therapy by lentiviral transduction could become a compelling alternative to allogeneic HSC transplantation, and thus may take center stage in the management of PIDs in coming years.